Magnetic mesoporous enzyme–silica composites with high activity and enhanced stability. Issue 6 (27th August 2015) - Cui, Jiandong; Feng, Yuxiao; Yue, Shu; Zhao, Yamin; Li, Linbo; Liu, Ronglin; Lin, Tao
Abstract: BACKGROUND: Encapsulation of enzymes in biomimetic silica seems to be a promising immobilization method due to mild processing conditions and short preparation time. However, biomimetic silica particles may be considered too small for industrial applications because they result in difficult recovery. Furthermore, the use of R5 peptide or polymers as catalyst usually causes protein denaturation. To overcome these drawbacks, a new stable and recyclable biocatalyst based on co‐encapsulation of magnetic nanoparticles and phenylalanine ammonia lyase (PAL) in biomimetic silica has been prepared using enzyme‐assisted direct condensation reactions of silicon oxide with tetramethoxysilane (TMOS). RESULTS: Under optimal conditions (10 mg mL −1 nanoparticles, 4.5 U mL −1 PAL, 0.8 mol L −1 TMOS), the highest activity recovery (52%) of encapsulated PAL was obtained. Compared with conventional PAL encapsulated in biomimetic silica (28%), the activity recovery was increased 1.86‐fold. TEM, CLSM, magnetisation measurements, and FTIR confirmed that the magnetic nanopaticles and PAL had been co‐encapsulated into the biomimetic silica. The resulting immobilized PAL exhibited higher activity and stability than native PAL, and the immobilized PAL can be easily separated by applying a magnetic field. CONCLUSIONS: This work provides a convenient strategy to prepare stable and easy recycled biocatalyst with excellent catalytic performance. © 2015 Society of Chemical Industry